Prosthetic Foot Mold Making with Photogrammetry Based Reverse Engineering Method - Lestari, Wahyu Dwi; Arif Hidayat, Muhammad (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
Prosthetic foot mold making is a crucial stage in the production of prosthetic feet that are in accordance with the anatomy and user needs. This research aims to develop a method for making prosthetic foot mold using a reverse engineering approach with photogrammetry techniques. The process begins with scanning the sole of the foot using photogrammetry methods to obtain a three dimensional model. The scanned model is then converted into a CAD design which is used as the basis for mold making. The mold design was made by considering ergonomic aspects and ease of manufacturing in the next stage. The results showed that the average deviation was within the range of ±0.65 mm or 0.42%, with a maximum deviation of 1.42%. This method is capable of producing precise casts that match the geometry of the original foot. With this approach, it is expected to improve the quality and customization of prosthetic products in the future.